The Impact of Educational Puzzle Games on the Cognitive Development of Children - Aliyudin, Ahmad; Alvionita, Yulia (Al Tahdzib: Jurnal Pendidikan Islam Anak Usia Dini, 2025)
Educational games play a vital role in supporting early childhood cognitive development through activities that stimulate motor skills, creativity, language, and logic while enhancing concentration, imagination, and learning engagement. This study aims to identify the differences in children's cognitive abilities before and after receiving an intervention through puzzle play as a learning stimulus. The research employed a quantitative approach with a one-group pretest-posttest design, involving 12 early childhood education students as the total sample. Data were collected through observation and analyzed using a Paired Sample t-Test. The analysis showed a significant difference between pre- and post-test scores, with a t-value of -10.721 and a significance level of 0.000, lower than 0.05. This indicates that puzzle play has a statistically significant positive effect on children's cognitive development. The mean difference of -5.333 suggests improvement after the intervention. Puzzle activities train logical thinking, instruction comprehension, and problem-solving skills. The teacher's role is essential in guiding the process. Conclusion: Puzzle play effectively enhances early childhood cognitive development by significantly improving concentration, logic, independence, and problem-solving in an enjoyable learning environment.